(untitled) (Research, Society and Development, 2021)
With its origins in buddhist practices, mindfulness aims to develop an awareness of what we are thinking, feeling, and doing in the present moment. The mindfulness practice has been gaining ground in western psychology since the 1700s, after that, its effectiveness in promoting mental health and remitting symptoms of mental disorders has been proven through scientific research. Therefore, it is necessary to draw a parallel with the covid-19 pandemic, which is impacting the psychological aspects of individuals, leading some to develop symptoms of anxiety and depression. Then, this study aims to analyze the importance of mindfulness practice as a tool to reduce anxiety and depression symptoms in the context of the covid-19 pandemic. Hence, the present work proposes to carry out a bibliographic survey through the Academic Google, SciELO, and PubMed platforms, categorizing the chapters of books and articles to analyze the results: a) mindfulness as an intervention to reduce symptoms of anxiety and depression and other mental disorders and; b) mindfulness as an intervention to reduce the stress symptoms caused in the population due to the covid-19 pandemic. Therefore, the results obtained in this bibliographic review points that mindfulness intervention is effective and efficient as a coping strategy for psycho-emotional suffering resulting from the covid-19 pandemic, being associated with prevention, promotion, and treatment of mental health.